Is There An Influence Of Visionary Leadership, Digital Leadership, And Knowledge Sharing On The Emotional Intelligence Of Generation Z Interns In DKI Jakarta? - Milda Putri, Marshanda; Emilisa, Netania; Wijaya, Rinninta; Triwira Adnan, Muhamad (LPPM STIE EKA PRASETYA, 2025)
Technological advancements have shaped Generation Z into creative, innovative, and adaptive digital native workers. This study analyzes the impact of Visionary Leadership, Digital Leadership, and Knowledge Sharing on Emotional Intelligence among Gen Z interns in DKI Jakarta. Using a quantitative approach, the study employed a survey method involving 151 respondents, analyzed through multiple linear regression. The findings reveal that Visionary Leadership, Digital Leadership, and Knowledge Sharing have a positive and significant effect on Emotional Intelligence. Visionary leaders enhance employees' emotional awareness and empathy through effective communication and long-term vision inspiration. Digital Leadership fosters collaboration through technology, while Knowledge Sharing creates a culture of knowledge exchange that strengthens interpersonal skills. This research provides valuable insights for organizations to optimize internship programs and leadership strategies to enhance the emotional competencies of young employees.